Secagem em camada de espuma das folhas de alecrim (Rosmarinus officinalis L.) - Souza, Juliana Barreto Pereira de (2021)
Rosemary (Rosmarinus officinalis L.), of the Benenden Blue variety, native to the Mediterranean region, has adapted in Brazil and today can be found in several parts. It is extremely widespread in gastronomy and cosmetology studies, because of aromatic and therapeutic properties. However, like any plant, rosemary can also deteriorate quickly and one of the ways to make the conservation possible is to use foam mat drying to removes the water after the transformation of the raw material into a stable foam, increasing the useful life and inhibiting microbial growth. Thus, the main purpose of this work was to obtain the rosemary powder through foam mat drying. The foam was form by juá (Ziziphus joazeiro Mart), natural foaming agent. The study followed the complete factorial experimental design of 2³ + 3 central points, 11 experiments, the independent variables being: concentration of foaming agent (4, 6, 8%), mix time (3, 5 and 7 minutes) and temperature drying time (50, 60 and 70 ° C) to verify its influence on drying time (dependent variable) and then characterize the powders. The physical-chemical characterizations of the powder (yield, solubility, total soluble solids, total titratable acid, pH, cytotoxicity and ashes) were compared to studies found in the literature on other types of dry leaves by the foam mat drying process and it was verified some disagreements As a result, it is concluded that the rosemary powder has low water solubility, with a better result of 22.06% ± 0.01, and total soluble solids value between 16.3 ± 0 , 9 º BRIX and 20.7 ± 0.5 º BRIX. The pH remained constant in all experiments. The cytotoxicological study carried out pointed out the non-toxicity of rosemary powder with juá below 500 ppm. The influence of the addition of the foaming agent was analyzed through the lyophilized powder for the analysis of total soluble solids, pH and total titratable acidity, whose comparison with the values of the 11 experiments did not present significant changes. Evaluating the experimental data of the three drying temperatures (50 ºC, 60 ºC and 70 ºC) it was concluded that the mathematical adjustment of Page’s model was the most adequate to the drying kinetics in foam mat of rosemary leaves with juá. Therefore, the best condition found for large-scale manufacturing was the maximum point (8%, 7 min, 70 ° C), as it presented the lowest water activity (aw), high yield (average of 91.79%), low moisture content, second best drying time (90 min) and greater acidity, determining factors to minimize microbiological proliferation and increase shelf life.